2020
DOI: 10.1007/s00784-020-03292-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonsurgical periodontal therapy on haematological parameters in grades B and C periodontitis: an exploratory analysis

Abstract: Aim Assessment of the effect of nonsurgical periodontal therapy on haematological parameters in patients with grades B (BP) and C periodontitis (CP). Methods Eight BP and 46 CP patients received full-mouth periodontal debridement within 48 h, if positive for Aggregatibacter actinomycetemcomitans with adjunctive systemic antibiotics (4 BP, 17 CP). Clinical data were collected prior and 12 weeks after periodontal therapy. Blood was sampled prior to and 1 day as well as 6 and 12 weeks after the first SD visit. Er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 30 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…In an in-vivo study of experimentally induced peri-implantitis in dogs, Chaushu et al showed that the induction of peri-implant disease caused a change in CBC values, which was corrected after surgical therapy [23]. Contrary to these findings, in a study of the effect of nonsurgical periodontal therapy on CBC parameters in 52 patients, whereas a clinical improvement in periodontal factors was noted, no significant changes in HGB or RBC counts were found [24].…”
Section: Discussionmentioning
confidence: 98%
“…In an in-vivo study of experimentally induced peri-implantitis in dogs, Chaushu et al showed that the induction of peri-implant disease caused a change in CBC values, which was corrected after surgical therapy [23]. Contrary to these findings, in a study of the effect of nonsurgical periodontal therapy on CBC parameters in 52 patients, whereas a clinical improvement in periodontal factors was noted, no significant changes in HGB or RBC counts were found [24].…”
Section: Discussionmentioning
confidence: 98%
“…This is the exploratory analysis of data of a prospective cohort study on the effect of SI on serum inflammatory parameters. An exploratory analysis of haematological parameters and heat shock protein 27 has been published recently [ 7 ]. Clinical examinations and therapy have been described in detail before [ 5 , 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…An exploratory analysis of haematological parameters and heat shock protein 27 has been published recently [ 7 ]. Clinical examinations and therapy have been described in detail before [ 5 , 7 ]. Thus, only a brief description is provided in the following.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations